2018
DOI: 10.1093/dnares/dsy026
|View full text |Cite
|
Sign up to set email alerts
|

Comparative mitochondrial genomics reveals a possible role of a recent duplication of NADH dehydrogenase subunit 5 in gene regulation

Abstract: Mitochondrial genome (mtDNA) carries not only well-conserved protein coding, tRNA and rRNA genes, but also highly variable non-coding regions (NCRs). However, the NCRs show poor conservation across species, making their function and evolution elusive. Identification and functional characterization of NCRs across species would be critical for addressing these questions. To this end, we devised a computational pipeline and performed de novo assembly and annotation of mtDNA from 19 Caenorhabditis species using ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…We also examined the mitochondrial genomes of JU1373 and NIC58, and found that the core functional complement is superficially identical; all 12 protein-coding, two ribosomal RNA, and 22 tRNA genes are called as present and intact in both ( Bernt et al, 2013 ; Lemire, 2005 ; Li et al, 2018 ). There are, however, several differences of unknown significance, including 12 missense variants in six of the core protein coding genes, the presence in NIC58 of a small non-coding region and a potentially novel (lowly expressed) gene encoding a 2-pass transmembrane protein, and differential expression at two additional loci ( Figure 8—figure supplement 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also examined the mitochondrial genomes of JU1373 and NIC58, and found that the core functional complement is superficially identical; all 12 protein-coding, two ribosomal RNA, and 22 tRNA genes are called as present and intact in both ( Bernt et al, 2013 ; Lemire, 2005 ; Li et al, 2018 ). There are, however, several differences of unknown significance, including 12 missense variants in six of the core protein coding genes, the presence in NIC58 of a small non-coding region and a potentially novel (lowly expressed) gene encoding a 2-pass transmembrane protein, and differential expression at two additional loci ( Figure 8—figure supplement 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The inferred antagonistic Medea in NIC58 may also involve novel protein-coding potential. We also examined the mitochondrial genomes of JU1373 and NIC58, and found that the core functional complement is superficially identical; all 12 protein-coding, 2 ribosomal RNA and 22 tRNA genes are called as present and intact in both (Bernt et al, 2013;Lemire, 2005;R. Li et al, 2018).…”
Section: Incompatibilities Are Associated With Duplicated and Novel Gmentioning
confidence: 99%
“…The strategy of single strand transcription from the mitochondrial genome is not just parochial to C . elegans ; it is a strategy used by many members of the genus Caenorhabditis [ 58 ]. If the unique strand transcriptional architecture of the Caenorhabditis mitochondrial genome is linked with production of dsRNA from the mitochondria, and if the release of mitochondrial RNA into the cytosol in mitochondrial mutants is the trigger for the formation of EOL-1 foci, we would expect a suppression of EOL-1 focus formation by shutting down mitochondrial RNA biogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…One of the possible reasons for the retention of gene copies and long non-coding regions in genomes is their potential functionality. For example, Li and colleagues proposed that the Nad5 -derived non-coding fragment in the Caenorhabditis briggsae mt genome upregulates the transcription of the neighboring Nad3 [ 120 ]. Transcribed copies of pseudogenes from non-coding regions of the nuclear and mt genomes were shown to participate in numerous processes of transcriptional and post-transcriptional gene regulation [ 121 , 122 ].…”
Section: Discussionmentioning
confidence: 99%